Diagnóstico y tratamiento del cáncer de mama HER2+: Guía de Práctica Clínica de la Sociedad Peruana de Cancerología - Morante, Zaida D. (2021)
Introduction. In Peru, breast cancer represents the most common type of cancer in women and the sixth most lethal type of cancer in the general population. Overexpression of the epidermal growth factor receptor (HER2 +) occurs in 20% to 30% of breast cancers, and is associated with more aggressive tumors, with greater recurrence and greater mortality. Objective. Prepare a set of evidence-based recommendations for the diagnosis and treatment of HER2 + breast cancer, in order to help reduce mortality, disease progression and improve quality of life. Methods. A panel of clinical specialists and methodologists was formed, who identified relevant clinical questions about the diagnosis and treatment of HER2 + breast cancer. A systematic search for CPGs was carried out in Medline (PubMed), and in developing and compiling agencies. For the formulation of recommendations, the panel of specialists discussed the evidence and elements of the context of implementation of the recommendation, following the methodology proposed by the Ministry of Health of Peru. Results. Nine clinical questions were prioritized. A total of 25 clinical recommendations were made. Conclusions. An evidence-based CPG was developed through a systematic, rigorous and transparent process developed by a multidisciplinary team.